2012
DOI: 10.1111/j.1755-3768.2012.02471.x
|View full text |Cite
|
Sign up to set email alerts
|

Thirty years of cornea cultivation: long-term experience in a single eye bank

Abstract: ABSTRACT.Purpose: To evaluate donor demographics, trends in donor tissue procurement and tissue storage over a long period. Methods: A retrospective, longitudinal, descriptive analysis was undertaken of data from the Hamburg Eye Bank Data Base (HEB-DB) that had been collected between 1981 and 2010. Data on 54 parameters of cornea donors [including clinical history, age, death cause, gender and death-to-explantation interval (DEI)] and of cultivated corneas (endothelial quality and development in culture, culti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 34 publications
0
28
0
Order By: Relevance
“…However, many studies have reported that corneas from advanced-age donors can also be sometimes used for transplantation, and thus donor age does not affect donor survival. Linke et al [17] showed that 32.1% of corneas from donors aged over 80 years met the appropriate criteria for transplantation. Patel et al [19] similarly demonstrated that 80% of corneas from advanced age donors had suitable standards for transplantation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, many studies have reported that corneas from advanced-age donors can also be sometimes used for transplantation, and thus donor age does not affect donor survival. Linke et al [17] showed that 32.1% of corneas from donors aged over 80 years met the appropriate criteria for transplantation. Patel et al [19] similarly demonstrated that 80% of corneas from advanced age donors had suitable standards for transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Our results did not reveal any significant difference between both sexes. Previous studies have shown a significant impact of time from donor death to cornea harvesting on endothelial count [17,27]. EBAA recommends cornea harvesting within 20 hours in those aged less than 50 years, and within 18 hours in those aged equal to or greater than 50 years of age [20].…”
Section: Discussionmentioning
confidence: 99%
“…Gavrilov and co-authors advocate an age limit of 80 or less, death to tissue retrieval time of less than 6 h and tissue retrieval to processing time of less than 24 h to minimize the percentage of discarded corneas (Gavrilov et al 2010). Linke et al cite the main factor in their comparatively low utilization rate of 43.5 % being a required minimum endothelial cell count of 2000 cells/mm 2 , higher than the requirement of most other countries (Linke et al 2013). However, with a minimum viable endothelial density of 2200 cells/mm 2 and viability of greater than 70 %, we still achieved a high utilization rate.…”
Section: Yearmentioning
confidence: 81%
“…Hemolysis mechanism interference is characterized as being not only from the hemoglobin but also the intracellular constituents, which are released into the serum or plasma during the hemolysis process (Dimeski et al 2012). Tissue donors usually succumb to Cardiorespiratory arrest (Linke et al 2013;Shiratori et al 2011), which is a factor that seems to increase blood hemolysis. In this study, only CLIA and ECLIAs had 100 % of IFUs which contained detailed information for hemolysis interference in blood test (Tables 1, 2, 3, 4).…”
Section: Interferences In Cadaveric Serological and Molecular Analysismentioning
confidence: 99%
“…Because of this report, the optimization of donor screening is being required worldwide (Ison et al 2011;Lai et al 2013;Len et al 2012). Brazilian Health Surveillance Agency (ANVISA) currently mandates that all tissue donors have to be screened for anti-HIV 1/2, anti-HBc, HBsAg and anti-HCV using ANVISA-licensed serological blood donor tests (Brasil 2008(Brasil , 2009.…”
Section: Introductionmentioning
confidence: 99%